2008
DOI: 10.1177/0091270007311572
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Dose Proportionality of Intramuscular Diazepam Administered by Autoinjector

Abstract: A diazepam 10-mg autoinjector was evaluated in bioequivalence and dose proportionality studies; both involved 24 young, healthy subjects and used randomized, open-label, 2-treatment, 2-period crossover designs with a 3-week washout period between treatments. The bioequivalence study compared a single diazepam 10-mg autoinjector with a conventional needle and syringe containing 10 mg of diazepam injectable. The dose proportionality study compared the pharmacokinetics of a single diazepam 10-mg autoinjector with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The initial precipitation observed with DZP reduced over time, possibly due to the precipitate being amorphous or a polymorph, which could readily redissolve. This supports reports of biphasic intramuscular absorption of DZP . Additionally, high inter‐individual variability was observed for absorption parameters ( C max and t max ) after intramuscular injection of DZP, resulting in clinical failure in some cases.…”
Section: Resultssupporting
confidence: 87%
“…The initial precipitation observed with DZP reduced over time, possibly due to the precipitate being amorphous or a polymorph, which could readily redissolve. This supports reports of biphasic intramuscular absorption of DZP . Additionally, high inter‐individual variability was observed for absorption parameters ( C max and t max ) after intramuscular injection of DZP, resulting in clinical failure in some cases.…”
Section: Resultssupporting
confidence: 87%
“…A Phase I study investigating bioequivalence and dose proportionality showed that DZP 10 mg auto-injection in the anterolateral thigh was bioequivalent to DZP injected with a conventional syringe [40]. In addition, this study also suggested that the site of injection is important because the gluteus or the deltoid muscles may lead to inconsistent absorption.…”
Section: Intramuscular Auto-injectionmentioning
confidence: 78%
“…Intramuscular diazepam administered by autoinjector as shown efficacy in the treatment of ARS [9,10] (Table 1) and appears to be rapidly absorbed [24,25]. Two studies in healthy volunteers demonstrated that intramuscular autoinjection was bioequivalent to intramuscular injection with a conventional syringe [24].…”
Section: Consider Alternative Formulations If Necessarymentioning
confidence: 99%
“…Two studies in healthy volunteers demonstrated that intramuscular autoinjection was bioequivalent to intramuscular injection with a conventional syringe [24]. Other studies found that diazepam administered intramuscularly by autoinjector was absorbed more rapidly than rectal diazepam [25], with slightly higher bioavailability [26].…”
Section: Consider Alternative Formulations If Necessarymentioning
confidence: 99%